2018
DOI: 10.1186/s42155-018-0012-6
|View full text |Cite
|
Sign up to set email alerts
|

Direct puncture embolisation of the non-coil-embolised internal iliac artery post EVAR - a novel use of the Angio-Seal closure device

Abstract: Background: Coil embolisation of the internal iliac arteries prior to EVAR is considered standard treatment to prevent a type 2 endoleak when extending an iliac limb into the EIA. Type 2 endoleaks that arise from a non-coil-embolised internal iliac artery can be challenging to treat due to difficult access. Case presentation: We present a case of a type 2 endoleak from the internal iliac artery that was not coiled prior to EVAR. This was treated with retrograde embolisation of the internal iliac artery via dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Embolization through retrograde, direct SGA access can solve all these issues as it allows a closer way to reach the target vessel without entering the peritoneal cavity or crossing the iliac bone eliminating associated risks. This approach has already been reported in recent years and during the literature review process we found 9 papers that utilized the same way for an overall amount of 10 patients4,6, [10,[22][23][24][25][26][27]. Direct surgical exposure or CT guided puncture of the SGA could have been an alternative4, [28], but both fluoroscopic roadmapping and sonographic guidance provided a good visualisation of the target vessel allowing its puncture with a mini-invasive approach.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Embolization through retrograde, direct SGA access can solve all these issues as it allows a closer way to reach the target vessel without entering the peritoneal cavity or crossing the iliac bone eliminating associated risks. This approach has already been reported in recent years and during the literature review process we found 9 papers that utilized the same way for an overall amount of 10 patients4,6, [10,[22][23][24][25][26][27]. Direct surgical exposure or CT guided puncture of the SGA could have been an alternative4, [28], but both fluoroscopic roadmapping and sonographic guidance provided a good visualisation of the target vessel allowing its puncture with a mini-invasive approach.…”
Section: Discussionmentioning
confidence: 97%
“…Embolization of the access site has been proposed [27] but the potential risk is represented by distal ischaemia. Alternatively, off-label use of arterial closure devices such as StarClose or Angio-Seal [24,26] can be utilized, but correct deployment of closure devices may be difficult when the target artery has a deep location and may require surgical exposure. Our strategy consisted of sheathless low-profile devices that made the arteriotomy very small.…”
Section: Discussionmentioning
confidence: 99%
“…Embolization through a percutaneous, retrograde, direct SGA access represents a simple way to reach the target vessel without entering the peritoneal cavity, crossing the iliac bone, or dealing with small collateral pathways. This approach has already been reported in recent years, and during the literature review process, we found nine papers that utilized the same method in 10 patients in total [5][6][7][8][9][10][11][12]16]. Direct surgical exposure or CT-guided puncture of the SGA could have been an alternative [10,27], but both fluoroscopic roadmapping and sonographic guidance provided a good visualization of the target vessel, allowing its puncture with a mini-invasive approach.…”
Section: Discussionmentioning
confidence: 99%
“…They are based on the compression of the site of puncture between a intravascular anchor and an absorbable extravascular plug (Aksoy et al 2006 ), assuring a durable exclusion of the trans-arterial tract. They have been chosen for the small amount of embolizing material is left in place within the vessel and because the shaft of the system (12 cm) is long enough to ensure a satisfactory control during deployment, even for deep punctures (Menon et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%